2016
DOI: 10.1016/j.bbalip.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid mediates non-canonical EGFR-MAPK activation through the induction of calcium signaling in colon cancer cells

Abstract: Obesity and a western diet have been linked to high levels of bile acids and the development of colon cancer. Specifically, increased levels of the bile acid deoxycholic acid (DCA), an established tumor promoter, has been shown to correlate with increased development of colorectal adenomas and progression to carcinoma. Herein we investigate the mechanism by which DCA leads to EGFR-MAPK activation, a candidate mechanism by which DCA may promote colorectal tumorigenesis. DCA treated colon cancer cells exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Previous reports have suggested that bile acid activates EGFR and TGR5 in the AGS cell line ( 23 , 24 ). In addition, bile acid activates EGFR in other cells lines, including colon cancer cells, cholangiocyte cells and esophageal adenocarcinoma cells ( 25 , 26 ). Whether the activation of EGFR and TGR5 is involved in the regulation of CDX2 requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that bile acid activates EGFR and TGR5 in the AGS cell line ( 23 , 24 ). In addition, bile acid activates EGFR in other cells lines, including colon cancer cells, cholangiocyte cells and esophageal adenocarcinoma cells ( 25 , 26 ). Whether the activation of EGFR and TGR5 is involved in the regulation of CDX2 requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A small amount of bile acids escapes the enterohepatic circulation and enters the colon; these bile acids are extensively metabolized by bacterial flora to form the secondary bile acids, deoxycholic acid (DCA), and lithocholic acid (LCA) [Dawson, ]. A large amount of evidence implicates DCA and LCA as endogenous cancer promoters [Baek et al, ; Centuori et al, ]. Feeding DCA to AKR/J mice, which are genetically resistant to the colon carcinogen azoxymethane (AOM), resulted in a significantly higher multiplicity of aberrant crypt foci compared to those in AOM‐exposed mice on a control diet [Flynn et al, ].…”
mentioning
confidence: 99%
“…Mitogen‐activated protein kinase (MAPK) pathway is one of the highly activated signaling pathways mediated by bile acids that induces hyper‐proliferation of colorectal mucosa and leads to colorectal tumor formation [Kyriakis and Avruch, ; Kundu et al, ]. DCA was demonstrated to stimulate MAPK signaling through epidermal growth factor receptor activation and calcium signaling in HT‐29 colon cancer cells [Centuori et al, ]. LCA was suggested to damage the epithelial lining of the gastrointestinal tract through reactive oxygen species production which results in resistance to apoptotic cell death and increased cell proliferation in gastrointestinal tract compartments [Kundu et al, ].…”
mentioning
confidence: 99%
“…As a member of the ErbB family, EGFR has an extracellular ligand‐binding domain and an intracellular portion that contains a tyrosine kinase domain. EGFR is most frequently activated by binding to its soluble ligands and then triggers a variety of signalling molecules that regulate intracellular signalling networks including Akt and MAPK pathway . In the Apc Min /+ mouse model, it has been shown that EGFR activity was important in the establishment of intestinal tumours, and Apc deficiency was associated with the increased EGFR activity .…”
Section: Discussionmentioning
confidence: 99%